If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -1 = 7x + 26 Reorder the terms: -1 + 4x = 7x + 26 Reorder the terms: -1 + 4x = 26 + 7x Solving -1 + 4x = 26 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -1 + 4x + -7x = 26 + 7x + -7x Combine like terms: 4x + -7x = -3x -1 + -3x = 26 + 7x + -7x Combine like terms: 7x + -7x = 0 -1 + -3x = 26 + 0 -1 + -3x = 26 Add '1' to each side of the equation. -1 + 1 + -3x = 26 + 1 Combine like terms: -1 + 1 = 0 0 + -3x = 26 + 1 -3x = 26 + 1 Combine like terms: 26 + 1 = 27 -3x = 27 Divide each side by '-3'. x = -9 Simplifying x = -9
| 15/12t^3-5/2t^2+0.8t=0 | | 2/3x+5+x=10 | | 3/8-19/28 | | 1/1-1/3 | | 17/20-3/8 | | 7(6/5-b)+3/5b=2/5(b+5) | | x^3+x=16 | | 7/15+3/10 | | f(t+1)=(t+1)2-7(t+1)+10 | | y=.35x-9.7 | | 4x+7-2x+12=x-4+6x | | -3/8x-3x2/-7 | | 10+5/6 | | q+11/25 | | -2/3-8 | | -2/3k-8 | | 3/(x-5)+7/(x+2)=5/(x^2-3x-10) | | 6x-4=2x+12+4x | | 4p+8/2p^2-8 | | 6x^2+25-9=0 | | 17x+19y=-29 | | 2c+79+8+c+3c-4+10=129 | | 3+2*5= | | 9p-q=59 | | n*2=8 | | 6/x+5=8/x | | -11+4c=7+5 | | 14x^2+5-[(7x^2-2)+4]= | | 2x^2-15=35 | | 4-x/2=6 | | 4x^3-6x^2+7x-23=0 | | 2y=10-x |